Prevalence of foodborne zoonotic pathogens in milk and milk products along the water buffalo milk value chain in Bangladesh - Shuvo Singha; Gerrit Koop; Md. Mizanur Rahman; Fabrizio Ceciliani; Md. Matiar Rahman Howlader (Revista Científica)
Buffalo milk and milk products are considered highly valued due to their superior nutritional quality and health benefits. Therefore, assessing the prevalence of zoonotic pathogens in buffalo milk is crucial for ensuring the safety of the consumers. The present study aimed to estimate the prevalence of important foodborne zoonotic pathogens in milk and milk products and identify the associated factors in the buffalo milk chain nodes in Bangladesh. One hundred and forty-three samples were collected from farm bulk milk (n = 34), middleman (n = 37), milk collection center (n = 37), and milk product shops (n= 35) and were analyzed using RT-PCR to estimate the prevalence of seven important zoonotic pathogens: Staphylococ cus aureus, Escherichia (E.) coli, Shiga toxin- producing Esch erichia (E.) coli O157:H7, Campylobacter (C.) jejuni, Listeria (L.) monocytogenes, Salmonella (S.) enterica, and Yersinia (Y.) enterocolitica. Escherichia coli was the most prevalent pathogen along the milk chain nodes. The prevalence of the pathogens was high over the buffalo milk value chain. Three classical enterotoxin- encoded genes for E. coli O157:H7 were tested e.g., eae, stx1, and stx2 of which the stx2 genotype was most prevalent and was most common in milk products (74%). The prevalence of L. monocytogenes and Y. enterocolitica were more prevalent on the farms (65 - 79%) than in the later milk value chain nodes. The prevalence of S. enterica was rather low (0 - 2.9%) in all the milk chain nodes and all the samples were negative for C. jejuni. These results suggest that buffalo milk consumers in Bangladesh are at risk for L. monocytogenes and Y. enterocolitica on the farms and E. coli O157:H7 with stx2 genotype at the milk product shops. S. enterica and C. jejuni are not frequent contaminants of the buffalo milk chain in Bangladesh. Avoiding plastic containers and dirty clothes for cleaning milk containers may help reduce contamination in the buffalo milk value chain.